PENGARUH MOTIF PENGGUNAAN APLIKASI LINE TERHADAP KEPUASAN PENGGUNA PADA MAHASISWA JURUSAN ILMU KOMUNIKASI DI KOTA PEKANBARU - Rian Ikrawansyah; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Along with the development of technology, communications, and information, this has resulted in developing a communication technology revolution, thereby encouraging the emergence of the smart phone is a smartphone. With smartphones today all the information from the figure, voice, text, and audio-visual equipment, can be processed quickly and easily, either by using the online application. Line is an instant messaging application, in which there are many more features such as free call services, games, emoticons, as well as the sticker that makes this line unique from the other instant messaging applications. Line Messenger are now being popular, ranging from small children to adults. In theory Uses and Gratification audience basically using the mass media based on certain motives, which the media considered trying to meet the needs of the audience. This study purpose to determine whether there is influence motive application use line against user satisfaction in communication science student majoring in Pekanbaru. The method used in this research is quantitative method of explanation , the data collection through questionnaires. Location of the research conducted in the department of communication sciences University of Riau and Riau Islamic University . The total sample of this study are 135 respondents . The Sampling Ttechniques is using unknown Populations . To know how much influence these two variables , the researchers used a simple linear regression analysis . For data processing questionnaire , carried out using statistics program Product And Service Solution ( SPSS ) Windows version 20 .Based on simple linear regression results for this study , the regression coefficient values obtained in this study is Y = 2,274+ 0.052 with a significance level of 0.0003 and smaller than α = 0.05 . Accordingto based on the determination test, the result amounted to 53.5 % . That means, there is the effect of being among the motives use online applications to user satisfaction in students majoring in communication science in Pekanbaru . While the remaining 46.5 % influenced by other indicators that are not included in this study . Thats mean H0 is rejected and Ha is accepted.Keywords : Motive, Satisfaction, and Line Aplication